The Impact Of Micro Finance On Poverty Reduction - Bahiru Wassie (My University, 2017)
The study was conducted using cross-sectional data collected from a total sample size of 120 randomly selected participant and non-participant rural and urban householdsFinote Selam Woreda of Amhara Regional State, Ethiopia. The aim of this study is measure the impact of Microfinance Program on households’ poverty reduction and to identify whether or not participation create employment opportunities and increase income of client households in the study area. The data collected were analyzed using descriptive and qualitative analysis and econometric models called Propensity Score Matching Model Approach. Applying a PSM technique, the study found that program participation has increased participant annual income by birr 7899.80 (38.83%), household asset was significantly increased by birr 14332.85 (27.10 %). The qualitative analysis result indicated that participation in microfinance program increase income of participant and creates employment opportunities for participant households. Finally, the study recommended that increase the existing services to the participant and extending the services to non-participants will also help the Microfinance Program attract the further unemployed communities, increase their income build their assets.
The Case Of Amhara Credit And Saving Institution (ACSI) In Finoteselam Woreda